Evaluation of Cocktail NSPase Inclusion in Reduced-Energy Corn-soybean Meal Diets on Live Growth Performance and Carcass Yield of Male Broilers - Walters, H.G.; Williams, M.P.; Latham, R.; Augspurger, N.; Brown, B.; Lee , J.T. (International Journal of Poultry Science, 2018)
Background and Objective: The objective of the current study was to evaluate the performance of broilers fed reduced-energy diets with the inclusion of nonstarch polysaccharide-degrading enzyme (NSPase). Materials and Methods: Three separate performance trials were conducted, with two of these trials evaluating processing yields in addition to growth performance. Each experimental design consisted of three dietary treatments including a positive control (PC), negative control (NC) with a 132 kcal kg–1 AME reduction throughout the experiments when compared to the PC and the NC supplemented with NSPase (NC+NSPase). All diets were corn and soybean meal based and contained distillers dried grains with solubles (DDGS). Experiments 1 and 3 consisted of 3 dietary phases including a starter (days 1-14), grower (days 15-28) and finisher (days 29-42) phase. Experiment 2 consisted of 4 dietary phases including a starter (days 1-14), grower (days 15-28), finisher (days 29-35) and withdrawal (days 36-42) phase. All experiments consisted of 10 replicates per treatment. At the conclusion of experiments 1 and 2, 6 broilers from each replicate were processed for carcass weight without giblets (WOG), fat pad and yield measurements on day 43. Results: In all experiments, the inclusion of NSPase increased body weight and improved feed conversion ratio (FCR) while also improving processing yields in experiments 1 and 2. In these trials, the NC diet yielded the lowest processing yields, while the inclusion of NSPase increased (p<0.05) multiple processing parameters when compared to the low-energy diet. Conclusion: These data confirm the ability of NSPase inclusion to improve performance and processing parameters in reduced-energy diets.